Flight control system design for autonomous UAV carrier landing - Fitzgerald, Pio (Cranfield University, 2004)
The challenge of integrating the UAV fleet into the carrier landing operational structure with respect to navigation and control strategies is addressed. A simulation model was developed which includes an aircraft model, an atmosphere model and an aircraft carrier motion model. The six degree of freedom non-linear aircraft model is based on the aerodynamic characteristics of the Mk 4a Jindivik extended to include rudder, spoiler and thrust vectoring controls, and an undercarriage model. The atmosphere model includes a carrier landing atmospheric disturbance model. The six degree of freedom aircraft carrier motion model is based on the ship motion simulation program SEAWAY. A Navigation System was developed which conforms to current operational procedures and future military navigation goals. This Navigation System continuously predicts the position in space where touchdown on the carrier deck will take place, based on aircraft position, the relative velocity between the aircraft and carrier, and the motion time history of the carrier. A reference flight path to the predicted touchdown point is continuously defined. The aircraft deviation from this flight path is determined and input to the autoland control system. For the purposes of this study perfection prediction is assumed. Automatic flight control systems were developed to assess three control strategies for suitability to the carrier landing task. The focus of this assessment was on vertical glide path deviation control. Direct Lift Control was compared to conventional control and was found to have superior performance, especially in turbulence. As UAV planforms tend to be tailless, and therefore lateral and pitch control are generated by a common aerodynamic surface, thrust vectoring was investigated as a means of alleviating aerodynamic pitch control requirements in the carrier landing task. An Adaptive Approach Speed Controller was developed as an extension of the Navigation System. This system synchronises the time that the aircraft passes over the stern, or ramp, of the carrier with the minimum absolute carrier pitch attitude attainable for a given range of approach speeds. This system was shown to be an effective method of minimising the negative effect that carrier motion has on the clearance between the aircraft and the carrier’s ramp.